Pengaruh Penggunaan Ampas Tahu Dalam Ransum Terhadap Performan Ayam Broiler - Zulfan Zulfan; Sulaiman Ibrahim (Jurnal Agripet, 2007)
ABSTRACT. The aim of this experiment is to investigate a possibility to include tofu by-product in broiler diet without causing adverse performances. This study was conducted in poulty production Lab. Faculty of Agriculture, Syiah Kuala University, Banda Aceh. The study performed 80 unsex day old chick, strain CP 707, Charoen Pokphan product, for which the chikens were divided into for diet treatment. The study was desingned into Completely Randomized Design (CRD) containing for different diet treatment. ei. R1 (Control diet with 0% of tofu by product. R2 (the diet containing 2.5% of tofu by-product), R3 (the diet containing 5% of tofu by-product, and R4 (the diet containing 7.5% of tofu by-product). Each treatment consisted of five chiks. Investigated variables included final body weight, body weght gain, feed consumption, feed conversion, and income over feed and chick coast (IOFCC). The data were analyzed by an analysis of variance and as a significant effect was detected, the analysis was continued by Duncan Multiple Range Test based on Steel and Torrie (1991). Result of this study showed that the inclusion of up to 5% of tofu by-product in the diet were not significantly defress body weight, body weight gain, feed consumpsion, and feed conversion compared to the control. However, the inclusion of 7.5% of tofu by-product significantly defress body weght, body weight gainfeed consumpsion. The was no significant effect on feed conversion as tofu by-product was included 7.5% in the diet. The inclusion of tofu by-product could minmize diet cost and increase. Income and Over Feed and Chick Cost (IOFCC). However, the highest IOFCC was detected in the untilization of 5% of tofu by-product was still possible to be included in poulty diet up to 5% without significantly depress broiler ferformances.Key word :Tofu by-product; Broiler diet; Body weight; Feed Consumption; Feed conversion